MICROBIAL CONTAMINATION TEST OF MIMOSA LEAVES SIMPLICIA - Kezia Joana Limarta; Luh Made Sudimartini; Anak Dharmayudha (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
The Mimosa plant (Mimosa pudica L.) is a wild plant that can be easily found in Indonesia and all of its parts have been used in traditional medicine, especially the leaves. Seeing its pharmacological content and benefits, the leaves of the Mimosa plant have the potential to be used as a simplicia as raw material for herbal medicine. This study aims to determine microbial contamination of mimosa leaves simplicia according to the General Standard Parameters of Medicinal Plant Extracts of the Ministry of Health of Republic of Indonesia in 2000 and Regulation of the Head of Food and Drug Monitoring Agency of Republic of Indonesia Number 32 Year 2019 concerning Quality Requirements for Traditional Medicines. This research is a non-experimental observational research with a comparative descriptive analysis design. The microbial contamination level was assessed by Total Plate Count (TPC) test and Total Yeast and Mold Count (TYMC) test. The research data obtained is quantitative data which was analysed by counting the number of microbes that grew on Plate Count Agar (PCA) media and Potato Dextrose Agar (PDA) media after being incubated at the appropriate growth temperature. The Total Plate Number of the Mimosa leaves sample is 3,9x104 CFU/gram and the Total Yeast and Mold Count is 2,5x103 CFU/gram. The results showed that the mimosa leaf simplicia met the microbial contamination requirements for Total Plate Number (£5x107) and Total Yeast and Mold Count (£5x105). It can be concluded that the mimosa leaves simplicia sample can be processed into drug preparations. Further research on pathogen Escherichia coli, Enterobacteriaceae, Clostridia, Salmonella, and Shigella microbial contamination and other quality standardization tests are needed.